Crosstalk between the endocannabinoid and mid-brain dopaminergic systems: Implication in dopamine dysregulation - Kibret, Berhanu Geresu; Canseco-Alba, Ana; Onaivi, Emmanuel S.; Engidawork, Ephrem (Frontiers in Behavioral Neuroscience, 2023)
Endocannabinoids (eCBs) and the expanded endocannabinoid system (ECS)-“endocannabinoidome”, consists of the endogenous ligands, eCBs, their canonical and non-canonical receptor subtypes, and their synthesizing and metabolizing enzymes. This system modulates a wide range of body functions and acts as a retrograde signaling system within the central nervous system (CNS) by inhibition of classical transmitters, and plays a vital modulatory function on dopamine, a major neurotransmitter in the CNS. Dopamine is involved in different behavioral processes and contributes to different brain disorders – including Parkinson’s disease, schizophrenia, and drug addiction. After synthesis in the neuronal cytosol, dopamine is packaged into synaptic vesicles until released by extracellular signals. Calcium dependent neuronal activation results in vesicular release of dopamine and interacts with different neurotransmitter systems. The ECS, among others, is involved in the regulation of dopamine release and the interaction occurs either through direct or indirect mechanisms. The crosstalk between the ECS and dopaminergic system has important inﬂuence in various dopamine-related neurobiological and pathologic conditions and investigating this interaction might help identify therapeutic targets and options in disorders of the CNS associated with dopamine dysregulation.